Pitaya (Dragon Fruit) (Hylocereus undatus) Pests and Beneficial Insects - Rita Elena Duncan; Daniel Carrillo; Jorge E. Peña (EDIS, 2021)
Pitaya or Dragon Fruit is a recent crop in South Florida; it belongs to the Cactaceae family, and its scientific name is Hylocereus undatus (Haworth) Britton & Rose. This fruit crop has grown rapidly and shows a good potential for commercialization. This fact sheet contains some of the pests and beneficial insects associated with it.